2021
DOI: 10.1039/d1ra07087h
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a surface type humidity sensor based on methyl green thin film, with the analysis of capacitance and resistance through neutrosophic statistics

Abstract: In this work, we propose a humidity sensor based on methyl green thin film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…From eqn (6) , the temperature increased and the conductivity decreased due to the change in atomic motion of the sensing layer and electrodes, hence the resistance of the sample increased but the capacitance decreased. There is an inverse relationship between resistance and capacitance (for LCR 40 ) as follows: Here, ‘ R ’ is the resistance and ‘ C ’ is the capacitance at the constant frequency of 1 kHz.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From eqn (6) , the temperature increased and the conductivity decreased due to the change in atomic motion of the sensing layer and electrodes, hence the resistance of the sample increased but the capacitance decreased. There is an inverse relationship between resistance and capacitance (for LCR 40 ) as follows: Here, ‘ R ’ is the resistance and ‘ C ’ is the capacitance at the constant frequency of 1 kHz.…”
Section: Resultsmentioning
confidence: 99%
“…A thin film of graphene nanoparticles was deposited on a glass substrate between two silver electrodes whose capacitance and resistance with respect to temperature and relative humidity were measured at 1 kHz with an LCR meter. The data were analyzed through classical and neutrosophic approaches (a similar analysis was performed for the interval data of the humidity sensor based on methyl green 40 ). Through this work, we have tried to develop an application of material statistics (a study in which data regarding material properties are analyzed through different methods of statistics) for the said graphene sensor's imprecise data based on modern statistics methods.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the capacitance of the sensor is increased as shown in Table 1 ; the capacitance of the sensor is increased from 0.62 to 6.23 pF with respect to the applied force of 0–0.7 N. Similarly, it is observed that the resistance of the sensor has decreased as the applied force increased. The resistance of a sensor can be written as 16 , 19 …”
Section: Resultsmentioning
confidence: 99%
“…Further, Afzal et al used a neutrosophic approach to analyze the capacitance and resistance of a humidity sensor. 26 Moreover, Aslam also worked and proposed different techniques using neutrosophic statistics. 27,28 In this work, we have fabricated a surface-type resistance temperature detector to measure the temperature of the robot skin.…”
Section: Introductionmentioning
confidence: 99%